LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) BERBASIS PROBLEM BASED LEARNING MENGGUNAKAN LIVEWORKSHEET PADA MATERI KIMIA HIJAU KELAS X SMA/MA - Putri, Rahma Yani; Erviyenny, Erviyenny; Herdini, Herdini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: This research aims to produce E-LKPD based on problem based learning using live worksheets on green chemistry material that is valid and suitable for use and to determine the response of teacher and student users to E-LKPD. This research uses a Research and Development (R&D) research design with a 4-D model (Define, Design, Develop, Disseminate) modified by 3-D (Define, Design, Develop). Validation results by material validators were based on appropriateness of content, PBL characteristics, language, presentation, appearance with a total percentage of 92.5%. Meanwhile, media validators were based on suitability of size, cover design and content design with a total percentage of 89.16% which was declared valid. The teacher and student responses respectively obtained a total percentage score of 94.62% and the student response was 88.79% with very good criteria.Key Words: Problem Based Learning, Green Chemistry, E-LKPD